Oxygen diffusion in the fluorite-type oxides CeO2, ThO2, UO2, PuO2, and (U, Pu)O2 - Kato, Masato; Watanabe, Masashi; Hirooka, Shun; Vauchy, Romain (Frontiers in Nuclear Engineering, 2023)
This study evaluates the self- diffusion and chemical diffusion coefficients of oxygen in fluorite-type oxides, CeO2 ThO2, UO2, PuO2, and (U, Pu)O2 using point defect chemistry (oxygen vacancies and interstitials). The self-diffusion coefficient changed in proportion to the 1/n power of oxygen partial pressure, similarly to the defect concentration. All parameters used to represent the diffusion coefficients were determined, and the experimental data were accurately stated. The oxides’ defect formation and migration energies were compared, and it was discovered that the change in Frenkel defect concentration affected the high-temperature heat capacities of CeO2 and ThO2. The oxygen chemical diffusion was evaluated in the oxides excluding ThO2, a line compound, and the coefficients increased dramatically around the stoichiometric composition, i.e., the chemical diffusion coefficient was much higher at O/M = 2.00 than in low O/M oxides. This difference altered the mechanism of the reduction and oxidation processes. In the reduction process, the chemical diffusion control rate was dominant, and a new phase with O/M = 2.00 was formed, and it expanded from the surface in the oxidation process from a low O/M ratio to O/M = 2.00.